In vitro evaluation of cytotoxic effects of di (2-ethylhexyl) phthalate (DEHP) produced by Bacillus velezensis strain RP137 isolated from Persian Gulf. (June 2021) - Pournejati, Roya; Gust, Ronald; Sagasser, Jessica; Kircher, Brigitte; Jöhrer, Karin; Ghanbari, Mohammad Mehdi; Karbalaei-Heidari, Hamid Reza
Abstract: Phthalates are widely used in polymer science and have potential toxicity related to their chemical structures. However, lots of evidence indicate that phthalate derivatives are undoubtedly produced as secondary metabolites by organisms, including plants, animals, and microorganisms. In the present study, Bacillus velezensis strain RP137 was cultured under optimized conditions. Its biomass was extracted with ethyl acetate with one fraction showing cytotoxic properties. A pure compound was isolated from the active fraction using combined silica gel and LH20 size exclusion column chromatography. Structural evaluation including FT-IR, 1 H NMR, 13 C NMR, HR-MS and CHN analysis identified the purified compound as di(2-ethylhexyl)phthalate (DEHP) with the formula C24 H38 O4 and the molecular weight of 389.29 Da. The microorganism-derived (stereospecific) DEHP was strongly reduced the proliferation and induced cytotoxic effects on various eukaryotic cell lines in compare to the synthetic racemic mixture of the compound when assessed by MTT assay. Furthermore, crystal violet assay and morphological changes confirmed the cytotoxic effect of DEHP. Interestingly, non-malignant SV40-immortalized fibroblast cells were less affected by the purified DEHP. Further evaluation on the antibacterial activity of DEHP documented no effect toward Gram-positive ( S. aureus ) and Gram-negative ( E. coli and P. aeruginosa ) pathogens even at a high concentration of 100 μM. In conclusion, existence of DEHP as byproduct of microorganism's metabolism can seriously be considered as a warning to human health. Highlights: Bacillus velezensis strain RP 137 produces DEHP through a secondary metabolism. DEHP showed strong cytotoxicity against various tumor cell lines (IC50  < 15 μM). Comparing IC50 data revealed the organism-derived DEHP is more cytotoxic than that of industrial origin. Urgent attention to investigate on deleterious effect of DEHP on human health is recommended.